Endoscopic Iliopsoas Fractional Lengthening After Total Hip Arthroplasty: Surgical Technique - Roger Quesada-Jimenez, M.D.; Ady H. Kahana-Rojkind, M.D.; Megan E. Flynn, M.D.; Isabella A. Wallace, B.A.; Dharma H. Patel, B.A.; Benjamin G. Domb, M.D. (Arthroscopy Techniques)
Iliopsoas tendinitis is a potential cause of persistent anterior hip pain after total hip arthroplasty. After infection and aseptic loosening are ruled out, the diagnosis is primarily based on clinical suspicion and radiographic analysis and is confirmed through ultrasound-guided injections. In refractory cases, surgical intervention may be required. We present a step-by-step endoscopic technique for fractional lengthening of the iliopsoas tendon. By addressing the tendon at the musculotendinous junction, this approach minimizes the impact on hip flexion and strength.